X+3y=66

Simple and best practice solution for X+3y=66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+3y=66 equation:


Simplifying
X + 3y = 66

Solving
X + 3y = 66

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-3y' to each side of the equation.
X + 3y + -3y = 66 + -3y

Combine like terms: 3y + -3y = 0
X + 0 = 66 + -3y
X = 66 + -3y

Simplifying
X = 66 + -3y

See similar equations:

| 2(14a+a)-6=24 | | 32+(z+91)=91+32-51 | | 30x-7=10 | | 3x-6=10x+15 | | 8(3/8)=20t(-1/8) | | (a+6)(a+4)= | | 3/7•3 | | 12+(13+y)=25+7 | | 450000-22000x=12000x+(-155000) | | 3x-7=x+14 | | X^2+8x+8=2x | | 3x-7=x+18 | | 450000-22000x=12000x+(155000) | | ydx+(x^2-4x)dy=0 | | (-3ln+lnx)=0 | | x^3-16x-16=0 | | X^2=-12x+64 | | 7+3(x-7)=1-5(x-6) | | -7k=-6k^2 | | -60=x^2-16x | | 2j^2-4j-30=0 | | (4x+3)+57=180 | | (-2x-50)(x+17)=0 | | 3X+42=84 | | 2x=(x+13)+62 | | -1+-4r=-20 | | 1+(6+14)=(1+x)+14 | | -2y+1=y+5 | | 3(32x-256)=0 | | (x-2)(-2x+1)=0 | | 6b^2+19b+15=0 | | 3.9x-6.47=2.5 |

Equations solver categories